Výběr a implementace informačního systému pro firmu - Hanyk, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato bakalářská práce se zabývá výběrem a implementací informačního systému pro podnik PORTABELL s.r.o. V práci jsou popsány teoretická východiska, metody, analýzy a technologie, které souvisejí s informačním systémem. Na základě analýzy požadavků podniku je vybrán odpovídající informační systém, pro který je vytvořen návrh postupu implementace.

This bachelor thesis deals with the selection and implementation of information systems for businesses PORTABELL limited liability. There are described theory,methods, and analysis technologies that are closely related of the information system. Based on the analysis of the requirements the company is selected, the corresponding information system which is designed draft of implementation process.
ICT Selection
Keywords: Informační systém; IS; podnikový informační systém; implementace; ABRA G2; implementační plán; ERP; Cloud Computing; Outsorcing; Information system; IS; business information system implementations; ABRA G2; implementation plan; ERP; Cloud Computing; Outsourcing